2016
DOI: 10.1248/yakushi.16-00036
|View full text |Cite
|
Sign up to set email alerts
|

How Patient-Pharmacist Communication Using the Drug Profile Book Relates to Patient's Behavior regarding Its Use

Abstract: This survey aimed to examine how patient-pharmacist communication using the drug proˆle book relates patient's behavior regarding its use. Among patients who visited one of theˆve pharmacies during the 4 months between July and October of 2013, 245 patients who had been prescribed antihypertensives were asked to complete a questionnaire. Items included patient attributes, whether the patient thought the drug proˆle book was useful to them (``sense of utility''), whether the patient has ever been questioned by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…It has been reported that patient-pharmacist communication resulting from the use of drug proˆle books has led to improvements in patients' medication awareness and behavior. 41) In addition, previous research has suggested that medication adherence improves when pharmacists su‹ciently explain medications through counseling. 42) Therefore, intervention by pharmacists, such as using drug proˆle books, could have a positive eŠect on medication adherence in elderly participants.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that patient-pharmacist communication resulting from the use of drug proˆle books has led to improvements in patients' medication awareness and behavior. 41) In addition, previous research has suggested that medication adherence improves when pharmacists su‹ciently explain medications through counseling. 42) Therefore, intervention by pharmacists, such as using drug proˆle books, could have a positive eŠect on medication adherence in elderly participants.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of sufficient information about the medical condition of their clients may prevent pharmacists in Japan from being confidently involved in depression care. Currently, the Japanese health care system is encouraging patients to bring their drug profile book to the pharmacy when they purchase prescription drugs, and its use contributes to preventing redundant prescriptions and possible drug interactions 43,44. This and other tools may help community pharmacists gain information on the comorbid conditions of their clients and become actively involved in depression care.…”
Section: Discussionmentioning
confidence: 99%
“…The main purpose for using a DPB in routine medical care is to prevent duplicate medications and drug interactions before they happen and to avoid adverse drug reactions. With each patient's agreement, the pharmacist issues him or her with a DPB in which information is accumulated about the drugs the patient has been prescribed by affixing "the sticker" in the book, mainly carrying details about prescriptions dispensed by pharmacies [5]. When receiving treatment by a medical institution, the patient brings the DPB and presents it to the physician and pharmacist, and the physician can take action at that time based on the DPB information.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it became clear that the patients' rate of bringing the DPB to their pharmacy (rate of bringing the DPB) was correlated to the patients' recognition of the role and sense of utility [9]. In addition, patients with experience of having been questioned by a pharmacist while looking at the DPB are known to have a higher rate of bringing the DPB, recognition of the role, sense of utility, and experience of showing the DPB to the physician [5]. However, because these empirical studies had a cross-sectional design, it was difficult to verify the effect of communication via DPBs.…”
Section: Introductionmentioning
confidence: 99%